Phenotypic Resistance to Rifampicin of Mycobacterium tuberculosis with the rpoB Leu430Pro Mutation - D. V. Belyaev; T. V. Umpeleva; D. V. Dianov; L. S. Lavrenchuk; T. Yu. Boteva; D. V. Vakhrusheva (Туберкулез и болезни лёгких, 2024)
The objective: to determine the role of the rpoB Leu430Pro mutation in the degree of phenotypic resistance of Mycobacterium tuberculosis to rifampicin.Subjects and Methods. The WHO classifies the rpoB Leu430Pro mutation of Mycobacterium tuberculosis as a borderline resistance mutation but of clinical significance. From an array of cultures, we selected and analyzed 14 isolates of M. tuberculosis with discrepancies in the results of molecular genetic and phenotypic testing, carrying only this mutation in rpoB. For all samples, the phenotypic resistance level (MIC) of these isolates to rifampicin was determined using BACTEC MGIT 960 and Middlebrook 7H11 medium.Results. It was found out that 12 of 14 isolates had the rifampicin MIC below the current critical concentration when tested by both methods, thus they were phenotypically sensitive. One isolate was resistant when tested with Middlebrook 7H11 but susceptible when tested with BACTEC MGIT 960. Only one isolate which had the additional rpoB F425L mutation demonstrated high-level phenotypic resistance when tested by the same tests. Our data indicate that the clinical significance of this mutation requires clarification since even a decrease in the critical concentration of rifampicin does not lead to unambiguous results of molecular genetic and phenotypic tests. It is necessary to standardize the use of various molecular genetic tests and principles of their clinical interpretation to optimize strategies for managing patients with tuberculosis caused by M. tuberculosis with the rpoB Leu430Pro mutation.